Research progress on Traditional Chinese Medicine nursing for elderly stroke patients with constipation (老年脑卒中患者便秘的中医护理研究进展) - LI Li (李黎); (李宁); CAO Hongjing (曹红京) (Association of Integrative Nursing, 2022)
This paper analyzed the potential factors causing constipation in elderly patients with stroke, and reviewed the studies on effect of Traditional Chinese Medicine (TCM) nursing in relief of constipation after stroke. Suggestions were provided for the further study and clinical practice of TCM nursing intervention on constipation in elderly stroke patients. (本文整理和分析引起老年脑卒中便秘的因素及采用中医护理措施改善老年脑卒中便秘的研究现状, 旨在为进一步深入研究中医护理对老年脑卒中便秘的应用提供参考和依据。)